2019
DOI: 10.2217/nnm-2018-0382
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Long-Term Fate of Superparamagnetic Iron Oxide-Based Nanoparticles Using Simulated Biological Fluids

Abstract: Aim: To simulate the stability and degradation of superparamagnetic iron oxide nanoparticles (MNP) in vitro as part of their life cycle using complex simulated biological fluids. Materials & methods: A set of 13 MNP with different polymeric or inorganic shell materials was synthesized and characterized regarding stability and degradation of core and shell in simulated biological fluids. Results: All MNP formulations showed excellent stability during storage and in simulated body fluid. In endosomal/lysosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 68 publications
8
25
0
Order By: Relevance
“…10,11 Studies of the long-term fate of the iron oxide nanoparticles in the body are still very limited. A few studies are devoted to in vitro degradation in simulated lysosomal conditions, 12,13 cell cultures, 14,15 and spheroids. 16 These studies showed some aspects of biotransformation of the magnetic particles, including a release of metal ions, involvement of the iron metabolic protein complex in iron scavenging, gradual transition of the particles to the form of ferritin, and a possibility of de novo particle synthesis from the degradation products.…”
mentioning
confidence: 99%
“…10,11 Studies of the long-term fate of the iron oxide nanoparticles in the body are still very limited. A few studies are devoted to in vitro degradation in simulated lysosomal conditions, 12,13 cell cultures, 14,15 and spheroids. 16 These studies showed some aspects of biotransformation of the magnetic particles, including a release of metal ions, involvement of the iron metabolic protein complex in iron scavenging, gradual transition of the particles to the form of ferritin, and a possibility of de novo particle synthesis from the degradation products.…”
mentioning
confidence: 99%
“…In these models, the authors deomstrated that metallic ions can be released due to the acidic pH of lysosomes after the uptake, exerting their action through an interaction with the thiol and selenol groups of the TrxR enzyme. Therefore, IONP degradation kinetic profiles were determined in ALF for both kinds of nanoparticles according to a procedure previously described [ 34 ] ( Figure S12 ). It is interesting to note that most of the nanoparticles were digested after 48 h of incubation.…”
Section: Resultsmentioning
confidence: 99%
“…ALF and BLF were prepared according to Rabel et al [ 34 ]. After membrane filtration (membrane cut-off: 14 kDa), the sterilized fluids were stored at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…To better understand the impact of coating materials on the IONs degradation and agglomeration profile, BIONs, ION@Dex, ION@PVA, and ION@PLGA were incubated in SBF, ALF, AEF, and PBS for 72 hours at 37 °C (Figure 4). In contrast to Rabel et al, a faster protocol was used here, which shortens the protocol to three days (vs. 28 days) [36]. Faster shaking speeds (1000 rpm vs 110 rpm) ensure that the particles are kept in suspension and therefore have more contact with the medium.…”
Section: Agglomeration and Fe 2+ -Release Studymentioning
confidence: 99%